Kiu - Hoshu - Ryu: Chusei Shingon mikkyd no shinso - Rappo, Gaétan (Japanese religions, 2016)
Review of Trenson, Steven. Kiu - Hoshu - Ryu: Chusei Shingon mikkyd no shinso. 祈雨•宝珠•龍: 中世真 言密教の深層. Rainmaking, Jewels, and Dragons: The Essence of Medieval Shingon Esoteric Buddhism. Publisher: Kyoto, Japan : Kyoto daigaku shuppankai, 2016. ISBN: 9784814000197